The reality of using flipped classroom-based education in the Arabic language department in the College of Basic Education / University of Diyala from the students’ point of view - Mohamed, Eskandar Ahmed (Al-Adab Journal, 2022)
The research aims to identify the reality of the use of flipped classroom-based learning in the Arabic language department in the College of Basic Education/University of Diyala from the students’ point of view. The researcher followed the descriptive analytical method (questionnaire) to identify the following: Exposing the obstacles facing the fourth stage students in the Arabic language department at the College of Basic Education / University of Diyala on learning based on flipped classrooms from their point of view. Detection of individual differences between the averages of students’ answers to the study tool related to the obstacles to learning based on flipped classrooms according to the gender variable (male and female). The questionnaire consists of (26) items, and the direction of each estimate was determined by dividing the range by the number of categories (2/3), to reveal the reality of using flipped classroom-based learning in the Department of Arabic Language at the College of Basic Education / University of Diyala from the students’ point of view. The researcher relied on the triple scale to answer the paragraphs: (Agree, Neutral, Disagree), the research sample included the entire research community, which is the fourth stage students in the Department of Arabic Language in the College of Basic Education for the academic year (2068) / 2068 for the academic year 2020/21. Male and female students, (33) male and (35) female students. The researcher used the following statistical methods: (T-test for one sample, T-test for two independent samples, arithmetic mean, standard deviation, Cronbach’s alpha correlation coefficient). In light of the researcher’s findings after analyzing the results and treating them statistically, he presented a set of recommendations and suggestions.